Analisis Nilai Tukar Nelayan Alat Tangkap Gillnet Di Kecamatan Parigi Kabupaten Pangandaran - Fakhry Hadiana; Atikah Nurhayati; Ine Maulina; Asep Agus Handaka Suryana (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
From the geographical condition, the potential of marine and fisheries resources in Indonesia is very large. There are many potentials that can be utilised by the community, especially people living in coastal areas. Therefore, many coastal communities make fisheries and marine resources a source of life and livelihood. However, this does not make the condition of the people living in the coastal area prosperous. analyse the exchange rate of gill net fishermen in Parigi Sub-district, Pangandaran Regency and analyse the factors that influence the exchange rate of gill net fishermen in Parigi Sub-district, Pangandaran Regency. This research uses quantitative descriptive analysis located in Parigi Sub-district, Pangandaran Regency. The research used purposive sampling method with 40 respondents. The data used in this study are primary and secondary data. This research analysis uses the Exchange Rate formula and Multiple Linear Regression Analysis. The average Exchange Rate of Gill Net Fishing Gear Fishermen in Parigi District is 109.72. This shows that the condition of Gill Net fishing gear fishermen in Parigi District is at a fairly prosperous level in meeting the needs of their households because the average obtained is> 100. Factors that influence the Fishermen's Exchange Rate include the Number of Family Dependents (X1), Work Deployment (X2), Income (X3), and Work Experience (X4).